Study of nasal packing versus quilting following septoplasty surgery - Sah, Kusheswar; Sigdel, Brihaspati; Nepali, Rajendra (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Nasal packing is a commonly performed procedure after septoplasty. Quilting is alternative procedure which reduces the complications of nasal packing. This study aims to compare the post-operative outcome of quilting and nasal packing following septoplasty.Methods: This is a prospective comparative study carried on 80 patients divided into two equal groups who had undergone quilting and nasal packing randomly after septoplasty surgery for symptomatic deviated nasal septum. Post-operative nasal outcome score, pain, haemorrhage, anxiety, infection was compared between two groups at 1st, 3rd, 7th and 30th post-operative days.Results: There was significant improvement in nasal obstruction post-operatively in quilting group (p